What's in a name? Unpacking “participatory” environmental monitoring - Turreira-García, Nerea; Lund, Jens; Domínguez, Pablo; Carrillo-Anglés, Elena; Brummer, Mathias; Duenn, Priya; Reyes-García, Victoria (Ecology and Society, 2018)
Turreira-García, N., J. F. Lund, P. Domínguez, E. Carrillo-Anglés, M. C. Brummer, P. Duenn, and V. Reyes-García. 2018. What's in a name? Unp acking “participatory” environmental monitoring. Ecology and Society 2 3(2):24. https://doi.org/10.5751/ES-10144-230224